Moonlighting enzymes of Borrelia burgdorferi - Jorge L. Benach (mBio, 2025)
ABSTRACT Moonlighting enzymes are increasingly recognized in bacteria with dual functions depending on whether they are intracellular or expressed on the surface. Enzymes of the glycolytic pathway are among the most frequently associated with moonlighting functions and lack the signal sequences needed to deliver them to the cell surface. Once these enzymes are on the surface, they perform functions that are associated with pathogenesis and development of infection through interaction with host substrates. One such interaction is adhesion. Borrelia burgdorferi, the etiologic agent of Lyme disease, must encounter a wide number of different tissues and substrates from ticks to mammalian hosts to complete its life cycle and persist. The phosphomannose isomerase of this organism has a moonlighting function, interacting with collagen IV, a main component of the basal lamina. It is abundant in the skin, which is the site of the initial infection of B. burgdorferi.